Principle of Human Rights Protection in view of Berlin Declaration - Oana - Măriuca Petrescu (Romanian Journal of European Affairs)
„[….] His dignity is inviolable. His rights are inalienable. Women and men enjoy equal rights. [….] We preserve in the European Union the identities and diverse traditions of its Member States. We are enriched by open borders and a lively variety of languages, cultures and regions. […] The European Union will continue to promote democracy, stability and prosperity beyond its borders”. Thus, Declaration of Berlin on the occasion of the fiftieth anniversary of the signature of the Treaties of Rome, as it was signed on 25th of March 2007 by all 27 members of European Union, is providing among others the principles and values based on respect of fundamental rights, common traditions of the member states, as well as promoting the variety of languages, cultures and regions within the EU. The European Union stresses out again its intention to protect the freedoms of citizens and their civil rights by all possible means, including in front of the courts.